Seekers ebook Island of shadows. - Hunter, Erin (Seekers: Return to the Wild, 2023)
"A companion to the wildly popular Seeker books . . . Reflecting the realities of the natural world, this new adventure will be greeted with delight." — Booklist The journey home begins . . . Toklo, Kallik, and Lusa survived the perilous mission that brought them together, and now it's time for them to find their way home. Kallik and Lusa are ready to be among their own kinds again, but Toklo, devastated by the loss of their companion Ujurak, feels hopeless and afraid of what's to come. When the group reaches a shadowy island covered in mountains and ice, Kallik is sure they're almost back to the Frozen Sea. But a terrifying accident leads them into a maze of abandoned tunnels, unlike anything they've ever seen before—making them question their path once again. The bears grow desperate for a sign to guide them, and when they meet a cub who has lost his whole family, Toklo believes the cub has been sent by Ujurak. But the others are unsure. Can they trust their new companion? Or could he be hiding something that will endanger them all?